Justification of the main functions of the model of scientific and methodological work in experimental secondary schools (Pedagogy of Higher and Secondary Education, 2012)
Hatsayuk N. Justification of the main functions of the model of scientific and methodological work in experimental secondary schools.In this article the basic functions of scientific-methodical work organization model in experimental secondary institutions were theoretically substantiated. Scientific-methodical work organization model was proved to serve as an instrument for scientific-methodical work system improvement through its functions opening. Scientific-methodical functions were analyzed, which were revealed in the modern scientists’ works
Keywords: experimental secondary institution; scientific-methodical work; model; function